Generation, Phenotyping and Functional Analysis of Dendritic Cells (DC) Derived from Human Monocytes and Acute Myeloid Leukaemia (AML) Cells - Lim, Moon Nian (2004)
Dendritic cells (DC) are efficient and potent antigen-presenting cells in our immune system. The ability of DC to present antigens and stimulate T cells has prompted their application as therapeutic cancer vaccines. The objective of this study was to generate DC from two resources: monocytes and AML blasts. The generated DC were evaluated for their morphology by phase contrast microscopy and May Grunwald Giemsa staining. Viability of cells was determined by trypan blue dye exclusion. Percentage of yields and immunophenotypes were carried out with flow cytometry. The functional capability of DC was also tested in Mixed Leukocyte Reactions and anti-leukaemia cytotoxicity assay. As a result, the generated DC shown typical morphology of those reported and expressed DC surface markers including CDl a, CD83, CD86, CD80 and HLA-DR. Down regulation of CD14 was also observed for cultured monocytes. In MLR assay, both generated DC elicited strong allo-stimulatory response up to more than 100 fold compared to preculture cells. Mild anti-leukaemia cytotoxicity effect (1 5%) was also observed fiom primed effector cells with AML antigen pulsed DC generated fiom monocytes. These data indicate that DC were successfully generated fiom the two resources and they were capable of eliciting immune response.